Appraisal of the impact of Dominant 20% SG on rice planthoppers and their natural enemies under North Indian Plains - Kooner, Rubaljot; Suri, K S; Makkar, G S; Singh, Gurmeet; Sharma, Rakesh; Kumar, Rajender (Indian Journal of Plant Protection, 2023)
Dominant 20 SG (dinotefuran 20% SG of M/s Insecticides India Ltd., Delhi), an insecticide of neonicotinoid class (blue toxicity label), was evaluated @ 20, 30 and 40 g a.i. ha-1 (100, 150 and 200 g ha-1, respectively) against rice planthoppers viz., brown planthopper (BPH) and the whitebacked planthopper (WBPH) infesting rice. The test insecticide was compared with the checks Chess 50 WG (pymetrozine) @ 300 g ha-1, Osheen 20 SG (dinotefuran) @ 200 g ha-1 and Ekalux 25 EC (quinalphos) @ 2000 ml ha-1. Dominant 20 SG showed increased efficacy in suppressing the BPH with increase in the concentration of the insecticide and days after spraying. Dominant 20 SG was statistically at par with the check, Osheen 20 SG recording 1.66 BPH/hill with 80.12 per cent suppression in BPH population after 3 days of insecticide application. Similar results with the test insecticide were also observed against whitebacked planthoppers. After 7 days of insecticide application, the test insecticide @ 40 g a.i./ha recorded population of 1.59 hoppers/hill (pooled mean of 5 locations) and it was at par with Osheen 20 SG (1.63 hoppers/hill). Highest paddy yield of 73.21 q/ha was obtained with Dominant 20 SG @ 200 g ha-1 which was statistically higher than the paddy yield of 72.96 q/ha in Osheen 20 SG @ 200 g ha-1. In basmati rice, Dominant 20 SG resulted in paddy yield of 35.15 q/ha, at par with the check, Osheen 20 SG (35.00 q/ha) at its highest dose of 200 g ha-1.